Utilization and Outcomes of Sentinel Lymph Node Biopsy for Vulvar Cancer - Cham, Stephanie (Obstet Gynecol, 2016)
OBJECTIVE: To examine the use and predictors of sentinel node biopsy in women with vulvar cancer. METHODS: The Perspective database, an all-payer database that collects data from over 500 hospitals, was used to perform a retrospective cohort study of women with vulvar cancer who underwent vulvectomy and lymph node assessment from 2006 to 2015. Multivariable models were used to determine factors associated with sentinel node biopsy. Length of stay and cost were compared between women who underwent sentinel node biopsy and lymphadenectomy. RESULTS: Among 2,273 women, sentinel node biopsy was utilized in 618 (27.2%), while 1655 (72.8%) underwent inguinofemoral lymphadenectomy. Performance of sentinel node biopsy increased from 17.0% (95% CI, 12.0-22.0%) in 2006 to 39.1% (95% CI, 27.1-51.0%) in 2015. In a multivariable model, women treated more recently were more likely to undergo sentinel node biopsy while women with more comorbidities and those treated at rural hospitals were less likely to undergo the procedure. The median length of stay was shorter for those undergoing sentinel node biopsy (median 2 days; IQR 1-3) compared to women who underwent inguinofemoral lymphadenectomy (median 3 days, IQR 2-4). The cost of sentinel node biopsy was $7599 (IQR, $5739-$9922) versus $8095 (IQR, $5917-$11,281) for lymphadenectomy. CONCLUSION: The use of sentinel node biopsy for vulvar cancer has more than doubled since 2006. Sentinel lymph node biopsy is associated with a shorter hospital stay and decreased cost compared to inguinofemoral lymphadenectomy.